Perspectives on research into spanish open woodlands (dehesa): some recent ecological experiences - Pineda, F D (Giornale botanico italiano, 1990)
Abstract Dehesa (open savanna-like woodland) is a Mediterranean ecosystem covering some two million hectares in the central, western and southeast parts of the Iberian Peninsula. Its importance as an ecosystem is seen from the perspective of food and energy production, scientific study and cultural traditions (Balcells et al., 1982 a, b; Humbert, 1980; Montoya, 1983; Ruiz, 1986; Vacher et al., 1985). Scientists have been carrying out studies from all of these perspectives for many years. Their conclusions have nevertheless had little influence on Spanish agricultural policy. While the information has been relevant and applicable to the ecosystem's management, policy has always been conditioned by controls on marketing channels, international stock-feed and agricultural machinery markets etc. This has led to a lamentable situation involving the destruction of landscapes, ancestral cultures and extensive grazing in large areas of the Iberian Peninsul (Balabanian, 1980; Campos Palicin, 1983; Fourneau Vacher et al., 1985). Some significant aspects of Spanish research in recent decades is summarized below, covering both the theoretical and the applied aspects of work done, particularly by the Ecology Department of Madrid's two Universities. Research on the dehesa in recent years has covered several phenomena: ? The conditioning factors imposed by climate and meteoroligical fluctuations in Mediterranean environments ? Types of herbivore grazing and pasture management ? Woodland-herbaceous vegetation interaction ? The perception and interpretation of landscapa by both its traditional users as well as others not involved in dehesa management ? Spatial plants organization observable on different scales of detail. Other aspects givin rise to several important studies include changes in land use and historic, institutional, economic, social and conservation question (Elena Rosellò, 1984; Garcia Sanz, 1978; Groome, 1985).
doi: 10.1080/11263509009428151
Keywords: conservation; Dehesa; Ecological succession; Mediterranean pastures; spatial organisation of plant communities